Who killed the poet? - Miranda, Luis de; Kover, Tina (UK Snuggly books, 2011)
When Bardo, an architect and poet, dies, his twin brothers first thought is to suspect the intriguing red-haired Ophelia, Bardos love, who has vanished. A chase across northern Europe commences, which is an elevating initiation to a dimension and understanding the brother narrator ignored. Through the voyage, the past reveals its real visage, while a mysterious child guides the characters to an unexpected climax.Under the guise of a flawless whodunit thriller, Who Killed the Poet? puts forward an original take on crucial themes, such as generational transmission, the politics of self-determination, and what it is to see life as it truly is, without undermining its complexity, diversity and poetry. A fictional manifesto for the 21st century, and a breathtaking translation of the seventh novel of an author at the peak of his art.